1989
DOI: 10.1126/science.2922595
|View full text |Cite
|
Sign up to set email alerts
|

Specific Recognition of Cruciform DNA by Nuclear Protein HMG1

Abstract: Cruciform DNA, a non-double helix form of DNA, can be generated as an intermediate in genetic recombination as well as from palindromic sequences under the effect of supercoiling. Eukaryotic cells are equipped with a DNA-binding protein that selectively recognizes cruciform DNA. Biochemical and immunological data showed that this protein is HMG1, an evolutionarily conserved, essential, and abundant component of the nucleus. The interaction with a ubiquitous protein points to a critical role for cruciform DNA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
414
0
6

Year Published

1994
1994
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 593 publications
(438 citation statements)
references
References 26 publications
10
414
0
6
Order By: Relevance
“…Structural transitions may be supported by other proteins that could stabilize or even promote the extrusion of the alternative conformations. The existence of proteins whose interaction with DNA is based on conformation ± but not sequence-speci®c ± recognition has been documented (Bianchi et al, 1988;Herbert et al, 1993;Leith and Russel, 1993;Pearson et al, 1995;Solaro et al, 1995). Transcriptional regulation of many genes involves conformational changes in DNA (Delic et al, 1991;Hanke et al, 1995;Iyer and Struhl, 1995;Spiro et al, 1995;Michelotti et al, 1996), and binding of some transcription factors depends on the conformation of DNA within or adjacent to their binding sites (Grigoriev et al, 1992;Spiro et al, 1993;Hu et al, 1994;May®eld and Miller, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Structural transitions may be supported by other proteins that could stabilize or even promote the extrusion of the alternative conformations. The existence of proteins whose interaction with DNA is based on conformation ± but not sequence-speci®c ± recognition has been documented (Bianchi et al, 1988;Herbert et al, 1993;Leith and Russel, 1993;Pearson et al, 1995;Solaro et al, 1995). Transcriptional regulation of many genes involves conformational changes in DNA (Delic et al, 1991;Hanke et al, 1995;Iyer and Struhl, 1995;Spiro et al, 1995;Michelotti et al, 1996), and binding of some transcription factors depends on the conformation of DNA within or adjacent to their binding sites (Grigoriev et al, 1992;Spiro et al, 1993;Hu et al, 1994;May®eld and Miller, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The A box or B box binds DNA in the minor groove despite of DNA sequence (Bonaldi et al, 2002). HMG boxes cause a significant bend in DNA and bind to the distorted DNA, such as four-way DNA junctions, cisplatin-damaged DNA and DNA mini-circles (Bianchi et al, 1989;Pil et al, 1992). Further studies indicate that A box is more effective than B box at binding to distorted DNA while B box has a higher preference for bending DNA and generating distorted DNA (Teo et al, 1995;Webb et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…The general function of acidic tail remains elusive despite its negatively regulations on HMG boxes. It downregulates the binding and bending ability of HMG boxes for linear DNA and distorted DNA although the binding affinity to DNA minicircles is unaffected (Bianchi et al, 1989;Pil et al, 1992;Stros et al, 1994;Pasheva et al, 1998;Lee et al, 2000). Several investigations have shown that the acidic tail binds to HMG boxes in vitro (Ramstein et al, 1999;Jung et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Rat HMG1 and human SRY are known to bind cruciform DNA in a sequence-independent fashion using the gel mobilityshift assay (44,49) and HMG-T from trout has been shown to bind a cruciform structure upstream of its own gene (50). The L-shape of the HMG-box might fit nicely with the angles formed between the arms of a cruciform, making such an interaction intuitively appealing.…”
Section: Methodsmentioning
confidence: 99%
“…HMG-box containing proteins have been shown in several cases to recognize structured nucleic acids such as cruciforms (44,49,50). Rat HMG1 and human SRY are known to bind cruciform DNA in a sequence-independent fashion using the gel mobilityshift assay (44,49) and HMG-T from trout has been shown to bind a cruciform structure upstream of its own gene (50).…”
Section: Methodsmentioning
confidence: 99%